Differential assembly of root-associated bacterial and fungal communities of a dual transgenic insect-resistant maize line at different host niches and different growth stages - Wen, Zhongling; Yao, Weixuan; Han, Mi; Xu, Xinhong; Wu, Fengci; Yang, Minkai; Fazal, Aliya; Yin, Tongming; Qi, Jinliang; Lu, Guihua; Yang, Rongwu; Song, Xinyuan; et al. (Frontiers in Microbiology, 2022)
Transgenic technology has been widely applied to crop development, with genetically modified (GM) maize being the world’s second-largest GM crop. Despite the fact that rhizosphere bacterial and fungal populations are critical regulators of plant performance, few studies have evaluated the influence of GM maize on these communities. Plant materials used in this study included the control maize line B73 and the mcry1Ab and mcry2Ab dual transgenic insect-resistant maize line 2A-7. The plants and soils samples were sampled at three growth stages (jointing, flowering, and maturing stages), and the sampling compartments from the outside to the inside of the root are surrounding soil (SS), rhizospheric soil (RS), and intact root (RT), respectively. In this study, the results of alpha diversity revealed that from the outside to the inside of the root, the community richness and diversity declined while community coverage increased. Morever, the different host niches of maize rhizosphere and maize development stages influenced beta diversity according to statistical analysis. The GM maize line 2A-7 had no significant influence on the composition of microbial communities when compared to B73. Compared to RS and SS, the host niche RT tended to deplete Chloroflexi, Gemmatimonadetes and Mortierellomycota at phylum level. Nitrogen-fixation bacteria Pseudomonas, Herbaspirillum huttiense, Rhizobium leguminosarum, and Sphingomonas azotifigens were found to be enriched in the niche RT in comparison to RS and SS, whilst Bacillus was found to be increased and Stenotrophomonas was found to be decreased at the maturing stage as compared to jointing and flowering stages. The nitrogen fixation protein FixH (clusters of orthologous groups, COG5456), was found to be abundant in RT. Furthermore, the pathogen fungus that causes maize stalk rot, Gaeumannomyces radicicola, was found to be abundant in RT, while the beneficial fungus Mortierella hyalina was found to be depleted in RT. Lastly, the abundance of G. radicicola gradually increased during the development of maize. In conclusion, the host niches throughout the soil-plant continuum rather than the Bt insect-resistant gene or Bt protein secretion were primarily responsible for the differential assembly of root-associated microbial communities in GM maize, which provides the theoretical basis for ecological agriculture.